Values of Local Wisdom in Traditional Ebeg Art in Patimuan Village, Patimuan District, Cilacap - ‘Aziz, Hudzaefi Assyifaul; Brata, Yat Rospia; Nurholis, Egi (JAMASAN: Jurnal Mahasiswa Pendidikan Sejarah, 2025)
This research aims to determine the development of Ebeg Traditional Art in Patimuan Village, Patimuan District, Cilacap, and to reveal the local wisdom values contained in Ebeg Traditional Art in Patimuan Village, Patimuan District, Cilacap. The method in this research uses qualitative methods using an ethnographic approach. The research instruments are observation, interviews and documentation. Data analysis techniques are carried out through the stages of data collection, data reduction, data presentation, and drawing conclusions. The results of the research show that Ebeg Traditional Arts have developed, and the local wisdom values of Ebeg Traditional Arts include; (1) Religious Values; (2) Social Values; (3) Cultural Values; (4) Artistic Value; (5) Historical Value; (6) Economic Value; (7) Value of Knowledge and Education; (8) Entertainment Value. The implications of this research are expected to serve as a reference for the development of strategies for preserving traditional arts based on cultural values, as well as strengthening local communities' awareness of the importance of preserving cultural heritage as a unifying force and determinant of identity.